2018
DOI: 10.1039/c8ra02961j
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of superficially and fully porous particles for HILIC separation of lanthanide–polyaminocarboxylic species and simultaneous coupling to ESIMS and ICPMS

Abstract: Application of sustainable chromatographic strategies to reduce effluent volumes generated by HILIC separation of lanthanide–polyaminocarboxylic acid species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…HILIC separations of Ln (Er, Eu, Gd, and Nd) with strong chelating molecules such as DTPA and EDTA have been previously investigated 13,31 and our first tests in this work showed that the nat Sm/ nat Nd–DTPA complexes were more retained than the complexes containing NM and TPAEN molecules. Hence, our efforts were first focused on the screening of the selectivity of several columns to separate nat Sm and nat Nd complexes of NM and TPAEN.…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…HILIC separations of Ln (Er, Eu, Gd, and Nd) with strong chelating molecules such as DTPA and EDTA have been previously investigated 13,31 and our first tests in this work showed that the nat Sm/ nat Nd–DTPA complexes were more retained than the complexes containing NM and TPAEN molecules. Hence, our efforts were first focused on the screening of the selectivity of several columns to separate nat Sm and nat Nd complexes of NM and TPAEN.…”
Section: Resultsmentioning
confidence: 70%
“…The instrumental configuration of the simultaneous coupling of HILIC in conventional separation format to ESIMS and the ICPMS XSeriesII was previously developed in the laboratory. 13 By applying this setup, the outflow from the column was split to enter the ESIMS with a flow rate of 295 µL min −1 (98.3%) and 5 µL min −1 for the flow entering the ICPMS (1.7%). A make-up made of 2% HNO 3 w/w and containing 10 ppb of 209 Bi as internal standard was added to the flow entering the ICPMS, with a flow rate of 140 µL min −1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As discussed earlier, SPP-HILIC is powerful for analyzing polar compounds, which is superior to TPP-HILIC for fast separations. It has been reported that SPP-HILIC phases have been used in quantitatively determining S-nitrosoglutathione in human plasma (Tsikas et al, 2013), in neuroscience such as the major inhibitory and excitatory neurotransmitters, γ-aminobutyric acid and L-glutamic acid (Defaix et al, 2018), and betaines and other quaternary ammoniumrelated compounds in bee pollen (Ares et al, 2020), in cosmetics to detect harmful impurities (Wang & Zhou, 2016), in the food industry such as amino acids and other components in dietary supplements (Themelis et al, 2017), and in the nuclear industry such as detecting lanthanide-polyaminocarboxylic species (Blanchard et al, 2018). It was also reported that HILIC phase can beneficially combine as a second dimension with a chiral column for comprehensive 2D LC (Bäurer et al, 2020).…”
Section: Hilic Separationsmentioning
confidence: 99%